Hepatitis B Virus-Specific Cellular Immunity Contributes to the Outcome of Occult Hepatitis B Virus Infection - Zhang, Weiyun; Luo, Shengxue; Li, Tingting; Wang, Min; Huang, Jieting; Liao, Qiao; Liu, Bochao; Rong, Xia; Li, Linhai; Allain, Jean-Pierre; Fu, Yongshui; Li, Chengyao (Frontiers in Microbiology, 2022)
There is little known of immunologic factors leading to the occurrence of occult HBV infection (OBI). Specific cellular immune response to HBV core/pol peptides was compared between blood donor populations, including 37 OBIs, 53 chronic HBV infections (CHB), 47 resolved infections or 56 non-infected controls, respectively. The rate of CD4+/CD8+ T cell proliferation in OBI or CHB carriers was higher than in HBV resolved and non-infected individuals (P<0.05). The intensity of IFN-γ-secretion T cell response of OBI carriers was highest, followed by CHB and resolved infections, and non-infected individuals (P<0.05). The frequency of intracellular IFN-γ and IL-17A CD4+/CD8+ and IL-21 CD4+ T cell responses was significantly higher in resolved infections than in OBI or CHB carriers (P<0.05), while the level of extracellular IL-17A of PBMCs was higher in OBI and CHB carriers than in resolved infections (P<0.01). The frequency of intracellular IL-10 CD4+ T cell response in CHB, OBI and resolved infections was higher than in HBV non-infected individuals (P<0.01). Intracellular IL-10 CD8+ T cell and extracellular IL-10 T cell responses were higher in CHB than in OBI (P=0.012) or HBV resolved infections (P<0.01). In conclusions, the higher level of effective T-cell response with IFN-γ, IL-17A and IL-21 contributes to resolved infection outcome, while higher level of suppressive T cell response with IL-10 results in HBV chronicity. OBI is an intermediary status between HBV resolved and chronic infections, in which IL-21 effector and IL-10 suppressor T cell responses play a crucial role in directing the outcome of HBV infection.